2016
DOI: 10.1002/14651858.cd011145.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Mini-Mental State Examination (MMSE) for the detection of dementia in clinically unevaluated people aged 65 and over in community and primary care populations

Abstract: The MMSE contributes to a diagnosis of dementia in low prevalence settings, but should not be used in isolation to confirm or exclude disease. We recommend that future work evaluates the diagnostic accuracy of tests in the context of the diagnostic pathway experienced by the patient and that investigators report how undergoing the MMSE changes patient-relevant outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
424
2
18

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 524 publications
(488 citation statements)
references
References 331 publications
7
424
2
18
Order By: Relevance
“…We developed charts that show expected normal cognitive trajectories compared with patients with dementia in an attempt to better discriminate the 2 populations over time. The accuracy of the cognitive charts is superior to percentile tables, 11,16,17,[34][35][36] which categorize patients into specific predetermined boxes, whereas ample data suggest that intervals in normative tables are not constant, being driven differently by age and education at different spectra of the continuum. 35 Our representative cases also clearly showed that a fixed cut-off does not accurately represent the longitudinal trajectory of an individual's cognitive performance.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…We developed charts that show expected normal cognitive trajectories compared with patients with dementia in an attempt to better discriminate the 2 populations over time. The accuracy of the cognitive charts is superior to percentile tables, 11,16,17,[34][35][36] which categorize patients into specific predetermined boxes, whereas ample data suggest that intervals in normative tables are not constant, being driven differently by age and education at different spectra of the continuum. 35 Our representative cases also clearly showed that a fixed cut-off does not accurately represent the longitudinal trajectory of an individual's cognitive performance.…”
Section: Discussionmentioning
confidence: 87%
“…34 All of these studies illustrated test distribution in normal scores. A recent Cochrane meta-analysis 35 evaluated the diagnostic accuracy of 18 different Mini-Mental State Examination cut points for dementia in people aged 65 years and older in community and primary care settings who had not undergone prior testing for dementia. The summary diagnostic accuracy of a cut point of 24 was a sensitivity of 85% and a specificity of 90%.…”
Section: Discussionmentioning
confidence: 99%
“…The classification of cognitive impairment was performed by using the scale's score and education level (Creavin et al, 2016) (Guerreiro et al, 1994): illiterate and ≤15 points; 1-11 years of education and ≤22 points; ≥11 years of education and ≤27 points. For these individuals only few socio-demographic and anthropometrics information were collected.…”
mentioning
confidence: 99%
“…The MMSE assesses global cognition with a well-established cut-off for cognitive impairment at <24 points that provides a high specificity [25,26]. AQT, on the other hand, provides a high sensitivity for impaired attention and executive function [23,27].…”
Section: Screening and Assessment Of Cognitive Impairmentmentioning
confidence: 99%